Risk Management Analysis of the Variability of External Factors in Business Planning Projects - Amalia Iskandriani; Tantri Yanuar Rahmat Syah; Suwarto; Rhian Indradewa (Jurnal Syntax Admiration, 2023)
The unemployment rate of graduates of the Diploma Three and Bachelor Programs is still very high, this happens because the competencies possessed by graduates do not match the qualifications requested by the company and there is also a decrease in the number of vacancies because they are still in the economic recovery period after the Covid 19 pandemic, so there is an imbalance between the number of vacancies and the number of job seekers and in the end the competition for jobs becomes tighter. This makes an opportunity for universities to build and develop a university whose graduates are able to compete in the world of work to meet customer needs and qualifications. One of them is Bina Insani University Bekasi which has the advantage of equipping graduates with competencies based on main hard skills, additional hard skills and soft skill competencies. to achieve its goals, business planning is carried out to improve the quality of its graduates, and to manage the variability of external factors, a thorough risk analysis is needed. This research uses qualitative research methods. The data collection technique in this research uses the literature study method. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that external factors can be analyzed using Porter's analysis and PETS analysis which then to deal with the variability of external factor threats in business planning projects, can be done by identifying risks, analyzing risks, evaluating risks, handling risks, communicating and consulting, monitoring and reviewing, finally recording and reporting risks. So that with a well-managed risk management function in each work unit, it is hoped that Bina Insani University Cikarang Campus can support the implementation of Good Corporate Governance in the company as a whole.